Nano fusiform Silicate-2 molecular sieve supported propane dehydrogenation catalyst as well as preparation method and application thereof
By using nano-funch Silicate-2 molecular sieve as a support to support the noble metal components, the problems of easy sintering of catalysts at high temperatures and accelerated side reactions in the prior art are solved, and a high stability and high selectivity propane dehydrogenation effect is achieved.
Patent Information
- Application Number
- CN202311370807.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing propane dehydrogenation catalysts are prone to sintering and inactivation at high temperatures, and the acidity of the support accelerates the occurrence of side reactions, resulting in catalyst coking inactivation and reduced selectivity of target products.
A nano-futuristic Silicate-2 molecular sieve was used as a support to synthesize a catalyst with a high specific surface area and multi-stage pore distribution by hydrothermal method, and loaded with precious metal components such as Pt and Sn additives to improve the dispersion and catalytic performance of the active components.
The stability and propylene selectivity of the propane dehydrogenation catalyst are significantly improved, the service life of the catalyst is extended, and the occurrence of side reactions is reduced.
Smart Images

Figure CN119869597A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of propane dehydrogenation catalysis, and in particular to a nano-fuselage Silicate-2 molecular sieve supported propane dehydrogenation catalyst and a preparation method thereof, as well as application of the catalyst in propane dehydrogenation. Background Art
[0002] Propylene is an important basic chemical raw material, and its downstream derivatives such as polypropylene, acrylonitrile, propylene oxide and acetone are important components of the three major synthetic materials: plastics, rubber and fibers. To date, propylene supply mainly comes from the by-products of traditional naphtha steam cracking and catalytic cracking. With the global energy structure changes and the trend of lightweight and diversified raw materials, the development of direct dehydrogenation (PDH) of propane, which is rich in resources, is the main development direction for the expansion of propylene production capacity in the future.
[0003] As an important proprietary propylene production process, direct propane dehydrogenation technology has the advantages of short process flow, high propylene yield, low investment cost and high economic efficiency. Currently, the industrialized propane dehydrogenation catalysts mainly include two categories: chromium series and platinum series. Among them, the former is chromium oxide / alumina (CrO2) produced by ABB Lummus. 2 O 3 / Al 2 O 3 ) catalyst, with fixed bed reaction process, although the propylene yield per pass is high, but the catalyst is very easy to carbonize and deactivate, need frequent regeneration (every 15-20 minutes), in addition, heavy metal Cr pollutes the environment, so its use is greatly restricted. The latter is based on UOP's catalyst loaded with platinum tin on alumina carrier (PtSn / Al 2 O 3 ) is mainly used in combination with a moving bed continuous reaction process to produce propylene. The advantages are high catalyst activity and good selectivity, but the disadvantage is that Al 2 O 3 The active components dispersed on the surface of the carrier are very easy to sinter and deactivate at high temperatures, and the acidity of the carrier itself is also easy to accelerate the occurrence of side reactions such as propane cracking and deep dehydrogenation during the catalytic process, resulting in catalyst coking and deactivation and reduced selectivity of the target product; the entire process cycle regeneration period is short, and the catalyst performance still needs to be further improved and perfected. Therefore, the development of a propane dehydrogenation catalyst with excellent performance, high propylene selectivity and good stability is the key to solving the technical problems of propane dehydrogenation.
[0004] A lot of research has been done to develop propane dehydrogenation catalysts with good performance.
[0005] CN111790384 A dehydrated Al 2 O 3As a carrier, any one of transition metal oxides, alkaline earth metal oxides or rare earth metal oxides is added as an auxiliary agent to regulate the interaction between Pt and Sn, so as to achieve high dispersion of the active component Pt and reduce Sn 4+ The reduction of γAl2O3 can accurately prepare a Pt-based multi-component catalyst that is stable at high temperatures, has low carbon deposition coverage, and has good durability; however, the catalyst preparation process requires multiple steps of impregnation and calcination, which is energy-consuming and cumbersome. Patent CN116212861A discloses a method for preparing a propane dehydrogenation catalyst using γAl2O3 as a catalyst. 2 O 3 Nanospheres were used as carriers, and Pt was diluted to a single-atom dispersion state using an excess of Sn additive to construct a PtSn disordered alloy sub-nanocatalyst. Although the stability of the catalyst was improved to a certain extent, the selectivity of propylene remained at 80-90%, which needs to be further improved.
[0006] In recent years, molecular sieve carriers have been used to replace traditional γ Al 2 O 3 The use of carriers for the dehydrogenation of propane to produce propylene has become a hot topic and a difficult point in research. US20120116143 A1 reported earlier a catalyst for preparing low-carbon olefins and a method for preparing low-carbon olefins. The catalyst is a solid catalyst containing MFI zeolite, which can effectively prepare olefins and has a long service life.
[0007] CN109746028B discloses a propane dehydrogenation supported catalyst and its preparation method, wherein a spherical aluminum-containing mesoporous molecular sieve silica gel composite material is prepared as a carrier, which includes a ball-milled aluminum component, a mesoporous molecular sieve material and silica gel. The carrier material has a special three-dimensional cubic ordered mesoporous channel distribution structure and a silica gel channel structure, and has a specific surface area of 100-180m 2 / g, so that the metal components are well dispersed inside its pores. After loading Pt, Sn, and Na components, the catalyst exhibits good propane dehydrogenation performance, with a propane conversion rate of 28%-30% and a propylene selectivity of about 80%. CN109746026A discloses a nanoporous all-silicon molecular sieve with an MFI structure, the particle size of which is 50-500nm and the specific surface area is 300m 2 / g or more, corresponding to a pore volume of 0.25cm 3 / g or more, at least one of the active components of Group VIII metals and at least one of Group IIB metals, rare earth metals, alkali metals and alkaline earth metals are introduced as additives into the above molecular sieves for catalytic dehydrogenation of propane to propylene, and the prepared catalyst has excellent catalytic activity and stability, and the propylene selectivity is 90.1%-95.8%. Other molecular sieve carriers, such as SAPO-34 and ZSM-5 composite carrier (CN112206816B), mesoporous MCM41 (CN201110283358.6) and SBA15 (CN112138705B, CN116273137A), etc., although they have made certain progress, are still in the basic research stage, and there are problems such as high synthesis cost, poor repeatability, structural stability and catalyst selectivity that need to be improved. There is still a lot of room for improvement in propane dehydrogenation catalysts and carriers. Therefore, the development of a carrier or catalyst with excellent performance is crucial to improving the performance of propane dehydrogenation catalysts. Summary of the invention
[0008] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a nano-shuttle-shaped Silicate-2 molecular sieve supported propane dehydrogenation catalyst and its preparation method and application. The present invention synthesizes a nano-sized shuttle-shaped Silicate-2 molecular sieve with rich pore structure and high surface area, and uses it as a carrier to prepare a supported propane dehydrogenation catalyst. The active components of the catalyst are more evenly dispersed, the contact area with the reaction gas propane is larger, the preparation method is simple, and it exhibits excellent propylene selectivity, high propane conversion rate and good stability in the process of catalytic propane dehydrogenation.
[0009] The first aspect of the present invention is to provide a nano-shuttle Silicate-2 molecular sieve supported catalyst, comprising a carrier and an active component and an auxiliary component supported on the carrier, wherein the active component is selected from at least one of the noble metal elements of Group VIII; the auxiliary component is selected from one or more of the metal elements of Group IVA, Group IA, and Group IIA;
[0010] Wherein, the carrier is Silicate-2 molecular sieve with nano-shuttle shape.
[0011] According to the preferred technical solution of the present invention, the particle size of the Silicate-2 molecular sieve is 180-500nm, and the specific surface area is 550m 2 / g or more, of which the external specific surface area is 180-450m 2 / g, pore volume at 0.5cm 3 / g and above, the pores present a multi-level pore distribution.
[0012] According to the preferred technical solution of the present invention, the Silicate-2 molecular sieve has at least one of the following characteristics:
[0013] The particle size of the Silicate-2 molecular sieve is 200-350 nm; and / or,
[0014] The specific surface area of the Silicate-2 molecular sieve is 550-700m 2 / g; and / or,
[0015] The pore volume of the Silicate-2 molecular sieve is 0.5-1.5 cm 3 / g; and / or,
[0016] The pores of the Silicate-2 molecular sieve present a multi-level pore distribution, with micropores having a pore size distribution of 0.5-2.0 nm and multi-level mesopores between crystals having a pore size distribution of 2-40 nm; preferably, the micropores have a pore size distribution of 0.5-1.0 nm and multi-level mesopores between crystals have a pore size distribution of 2-30 nm.
[0017] According to the preferred technical solution of the present invention, the Silicate-2 molecular sieve presents a shuttle-shaped morphology assembled by plugging rod-shaped microcrystals, and the preferred grain size is 200-400 nm.
[0018] According to a preferred technical solution of the present invention, the Silicate-2 molecular sieve is an all-silicon MEL structure molecular sieve.
[0019] According to a preferred technical solution of the present invention, the Silicate-2 molecular sieve is prepared by the following method: the preparation method of the Silicate-2 molecular sieve comprises subjecting a mixture containing a silicon source, a template and water to hydrothermal crystallization treatment, cooling the obtained reaction mixture, and then subjecting the mixture to solid-liquid separation, optional washing, optional drying, and calcination to obtain the Silicate-2 molecular sieve.
[0020] According to the preferred technical solution of the present invention, the preparation method comprises the following steps:
[0021] (1) mixing a silicon source, an organic template and water to form a mixed gel;
[0022] (2) subjecting the mixed gel to a hydrothermal crystallization treatment to obtain a reaction mixture;
[0023] (3) After the reaction mixture is cooled, preferably to room temperature, solid-liquid separation, optional washing, optional drying, and calcination are performed to obtain the Silicate-2 molecular sieve.
[0024] According to the preferred technical solution of the present invention, SiO 2The molar ratio of the silicon source to the template and water is 1:(0.10.5):(10-50), more preferably 1:(0.150.4):(10-30).
[0025] According to a preferred technical solution of the present invention, the silicon source is an organic silicon source, preferably at least one of tetraethyl orthosilicate, tetraethyl orthosilicate, tetraethyl silicate-28, and tetraethyl silicate-40.
[0026] According to a preferred technical solution of the present invention, the organic template is one or more of tetrabutylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium fluoride, and cyclohexylamine, preferably tetrabutylammonium hydroxide and tetrabutylammonium bromide are used as templates; more preferably, tetrabutylammonium hydroxide.
[0027] According to the preferred technical solution of the present invention, the mixing conditions in step (1) include: temperature of 20-30°C and time of 3-12h; preferably, relative to 10g of the mixture system, the mixing method is stirring, and the preferred stirring speed is 400-600rpm.
[0028] According to a preferred technical solution of the present invention, the conditions for the hydrothermal crystallization treatment include: a temperature of 120-190° C., preferably 120-170° C., and / or a time of 36-150 h, preferably 72-120 h.
[0029] The solid-liquid separation in step (3) is performed by centrifugation. Preferably, the centrifugation conditions include: a rotation speed of 3000-5000 rpm and a time of 0.5-2.0 h.
[0030] The washing in step (3) is performed with deionized water. The method of the present invention has no particular limitation on the amount of water and the number of times of the washing. It is only necessary to clean the free ions and the precursor solution, and the final pH value can be 7.0-7.5.
[0031] The drying conditions in step (3) include: temperature of 80-120° C. and time of 6-10 h.
[0032] According to the preferred technical solution of the present invention, the calcination conditions include: heating to 500-600°C, preferably 550-580°C, at a heating rate of 1-2°C / min; and calcination time of 4-6h.
[0033] The Silicate-2 molecular sieve obtained by the above specific preparation method of the present invention has a particle size of 180-500nm and a specific surface area of 550m 2 / g or more, of which the external specific surface area is 180-450m 2 / g, pore volume at 0.5cm3 / g and above, the pores present a multi-level pore distribution.
[0034] Preferably, the particle size of the Silicate-2 molecular sieve is 200-350 nm.
[0035] Preferably, the specific surface area of the Silicate-2 molecular sieve is 550-700m 2 / g.
[0036] Preferably, the pore volume of the Silicate-2 molecular sieve is 0.5-1.5 cm 3 / g.
[0037] Preferably, the pores of the Silicate-2 molecular sieve present a multi-level pore distribution, with micropores having a pore size distribution of 0.5-2.0 nm and intercrystalline multi-level mesopores having a pore size distribution of 2-40 nm; preferably, the micropores have a pore size distribution of 0.5-1.0 nm and the intercrystalline mesopores have a pore size distribution of 2-30 nm.
[0038] The nano-shuttle-shaped Silicate-2 molecular sieve prepared by the method is more preferably a full-silicon MEL structure molecular sieve, and the Silicate-2 molecular sieve presents a shuttle-shaped morphology of rod-shaped microcrystals plugged and assembled, and has a specific surface area of up to 550-700m 2 / g, of which the external specific surface area is 180-450m 2 / g, pore volume is 0.5-1.5cm 3 / g, the pores are distributed in a multi-level manner, and the pore size of micropores is distributed in the range of 0.5-1.0nm, and the multi-level mesopores between crystals are distributed in the range of 2-30nm.
[0039] According to the present invention, the active component is selected from at least one of the noble metal elements of Group VIII; according to a preferred technical solution of the present invention, the active component is selected from at least one of Pt, Ir, Au, Pd, and Rh, and further preferably, the noble metal active component is Pt.
[0040] According to the present invention, the auxiliary agent component is selected from one or more of the metal elements of Group IVA, Group IA, and Group IIA; according to a preferred technical solution of the present invention, the auxiliary agent component is selected from at least one of the metal elements of Group IVA, and / or, the alkali metals of Group IA, and the alkaline earth metal elements of Group IIA;
[0041] Preferably, the auxiliary agent component is selected from at least one of the metal elements of Group IVA Sn, and / or the alkali metals of Group IA Na, K, Rb, Cs, and the alkaline earth metal elements of Group IIA Mg, Ca, and Sr.
[0042] According to a preferred technical solution of the present invention, the morphology of the catalyst is a nano-spindle-shaped sphere assembled by plugging and assembling rod-shaped and flake-shaped microcrystals.
[0043] According to a preferred technical solution of the present invention, the size of the catalyst is 200-500 nm.
[0044] According to a preferred technical solution of the present invention, the particle size of the active component in the catalyst is 2-10 nm.
[0045] The catalyst provided by the invention loads active components and auxiliary agents on the Silicate-2 molecular sieve, and the active components, auxiliary agents and molecular sieve can play a synergistic role with each other to obtain a higher propane dehydrogenation conversion rate and propylene selectivity in the reaction of propane dehydrogenation to propylene.
[0046] According to a preferred technical solution of the present invention, based on the total mass of the catalyst as 100wt%, the loading amount of the active component is 0.1wt%-1.0wt%, preferably 0.1wt%-0.5wt%, and / or the loading amount of the metal element of Group IVA is 0.1wt% 2.0wt%, preferably 0.1wt%-1.5wt%, and / or the loading amount of the metal element of Group IA is 0wt% 1wt%, preferably 0.1wt%-1.0wt%, and / or the loading amount of the metal element in Group IIA is 0-2.0wt%, preferably 0.1wt%-1.0wt%.
[0047] As an example, according to a further more preferred technical solution of the present invention, based on the total mass of the catalyst as 100wt%, the loading amount of the precious metal active component Pt is 0.1wt%-1.0wt% of the total mass of the catalyst, and more preferably 0.1wt%-0.5wt%; the loading amount of the Sn additive metal is 0.1wt%2.0wt% of the total mass of the catalyst, and more preferably 0.1wt%-1.0wt%; optionally containing alkali metal or alkaline earth metal additives, when containing additives, the loading amount of the alkali metal and alkaline earth metal additives is preferably 0.1wt% 1.0wt% of the total mass of the catalyst.
[0048] According to a preferred technical solution of the present invention, the total mass of the carrier, active component and auxiliary component is 100wt%.
[0049] The second aspect of the present invention is to provide a method for preparing the catalyst described in the first aspect, comprising loading the active component source and the auxiliary component source on the carrier, and then obtaining the catalyst by calcination.
[0050] According to a preferred technical solution of the present invention, the calcination conditions include: heating at a rate of 1-2°C / min to a temperature of 550-600°C, and calcination time of 4-6h.
[0051] According to the preferred technical solution of the present invention, the active component and the auxiliary metal component are loaded onto the nano-fuselage Silicate-2 molecular sieve by an impregnation method to prepare the catalyst.
[0052] Preferably, the loading method is to immerse the carrier in a solution containing the active component source and the auxiliary component source, and then remove the solvent; preferably,
[0053] The solution containing the active component source and the auxiliary component source is an aqueous solution; further preferably,
[0054] The active component source is water-soluble, and / or the auxiliary component source is water-soluble.
[0055] According to the present invention, preferably, the amount of the active component source, the auxiliary component source, and the carrier is such that, based on the total mass of the catalyst being 100wt%, the loading amount of the active component is 0.1wt%-1.0wt%, preferably 0.1wt%-0.5wt%; and / or, the loading amount of the metal element of Group IVA is 0.1wt% 2.0wt%, preferably 0.1wt%-1.5wt%; and / or, the loading amount of the metal element of Group IA is 0wt% 1wt%, preferably 0.1wt%-1.0wt%; and / or, the loading amount of the metal element in Group IIA is 0-2.0wt%, preferably 0.1wt%-1.0wt%.
[0056] The carrier is a Silicate-2 molecular sieve having a nano-shuttle shape.
[0057] As mentioned above, according to the preferred technical solution of the present invention, the particle size of the Silicate-2 molecular sieve is 180-500nm, and the specific surface area is 550m 2 / g or more, of which the external specific surface area is 180-450m 2 / g, pore volume at 0.5cm 3 / g and above, the pores present a multi-level pore distribution.
[0058] According to the preferred technical solution of the present invention, the Silicate-2 molecular sieve has at least one of the following characteristics:
[0059] The particle size of the Silicate-2 molecular sieve is 200-350 nm; and / or,
[0060] The specific surface area of the Silicate-2 molecular sieve is 550-700m 2 / g; and / or,
[0061] The pore volume of the Silicate-2 molecular sieve is 0.5-1.5 cm 3 / g; and / or,
[0062] The pores of the Silicate-2 molecular sieve present a multi-level pore distribution, with micropores having a pore size distribution of 0.5-2.0 nm and multi-level mesopores between crystals having a pore size distribution of 2-40 nm; preferably, the micropores have a pore size distribution of 0.5-1.0 nm and multi-level mesopores between crystals have a pore size distribution of 2-30 nm.
[0063] According to the preferred technical solution of the present invention, the Silicate-2 molecular sieve presents a shuttle-shaped morphology assembled by plugging rod-shaped microcrystals, and the preferred grain size is 200-400 nm.
[0064] According to a preferred technical solution of the present invention, the Silicate-2 molecular sieve is an all-silicon MEL structure molecular sieve.
[0065] As an example, according to the preferred technical solution of the present invention, the steps of preparing a catalyst by loading the active component and the auxiliary metal component onto the nano-shuttle Silicate-2 molecular sieve by an impregnation method include the following:
[0066] (1) Based on the total mass of the catalyst, the active component precious metal component Pt source, and / or the auxiliary metal component Sn source, and / or the alkali metal auxiliary K source are weighed in accordance with their respective corresponding mass percentage ratios, dissolved in deionized water, stirred and mixed evenly, and added to the above-mentioned nano-shuttle Silicate-2 molecular sieve, and fully immersed for a certain period of time so that the metal components are fully dispersed on the surface of the molecular sieve;
[0067] (2) The impregnated nano-fuselage Silicate-2 molecular sieve is subjected to rotary evaporation to remove the solvent, dried and calcined in sequence to obtain a nano-fuselage Silicate-2 supported catalyst.
[0068] The active component noble metal Pt source in step (1) can be selected from platinum nitrate, platinum chloride, diammine platinum tetrachloride, tetraammine platinum nitrate, chloroplatinic acid, preferably chloroplatinic acid H 2 PtCl 6 6H 2 O;
[0069] The auxiliary metal Sn source in step (1) includes one of crystalline tin tetrachloride and tin dichloride, preferably crystalline tin tetrachloride SnCl 4 ·5H 2 O.
[0070] The alkali metal or alkaline earth metal auxiliary agent source in step (1) includes one of its nitrate, sulfate and chloride, preferably nitrate or chloride.
[0071] Further preferably, based on the total mass of the catalyst, the loading amount of the precious metal active component Pt is 0.1wt%-0.5wt% of the total mass of the catalyst; the loading amount of the Sn promoter metal is 0.1wt%1.0wt% of the total mass of the catalyst; and or the loading amount of the alkali metal and alkaline earth metal promoter is 0.1wt%0.5wt% of the total mass of the catalyst.
[0072] The stirring conditions in step (2) include: a temperature of 20-30° C., a time of 10 to 30 min; and a stirring speed of 400-600 rpm relative to 10 g of the mixture system.
[0073] Preferably, during the immersion process, the temperature is 20-30° C. and the time is 4-6 hours.
[0074] The conditions for rotary evaporation in step (2) include: a water bath temperature of 70-80° C., a rotary speed of 120-150 rpm, and a vacuum degree of 75-65 mbar.
[0075] The drying conditions in step (2) include: a temperature of 80-120° C. and a drying time of 6 to 10 hours.
[0076] Preferably, the calcination conditions in step (2) include: a heating rate of 1-2°C / min, a temperature of 550-600°C, and a time of 4-6h.
[0077] The third aspect of the present invention is to provide an application of the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect in propane dehydrogenation catalysis.
[0078] Preferably, the application is a propane dehydrogenation method, comprising contacting propane with the catalyst, and carrying out a propane dehydrogenation reaction in a hydrogen atmosphere to obtain propylene.
[0079] As an example, preferably, the application includes: loading the catalyst into a reactor, and using H as the reaction gas. 2 diluting, and performing a dehydrogenation reaction to obtain propylene; more preferably,
[0080] Propane gas mass space velocity is 1-50h -1 , and / or, H 2 The feed pressure ratio of propane is 1:1-1:8, and / or the dehydrogenation reaction temperature is 550-620°C.
[0081] Compared with the prior art, the present invention has the following beneficial effects:
[0082] (1) The catalyst provided by the present invention uses a nano-shuttle-shaped Silicate-2 molecular sieve with a MEL structure synthesized by a hydrothermal method to replace the traditional Al 2 O 3 The carrier can greatly reduce propane cracking, deep dehydrogenation and carbon deposition during the dehydrogenation process, effectively solve the problem of frequent regeneration of industrial propane dehydrogenation catalysts, improve the selectivity of propylene, and extend the service life of the catalyst;
[0083] (2) The catalyst provided by the present invention is more 2 O 3 The carrier and commercially purchased ZSM-11 molecular sieve have larger specific surface area and pore volume, which can significantly improve the dispersion of loaded active components, reduce particle agglomeration, and increase the distribution content of active components and additives in the molecular sieve pores; at the same time, the two-dimensional cross-cross straight-through pore MEL structure and rich pore distribution characteristics of Silicate-2 molecular sieve can effectively promote the diffusion process of propane and product propylene in the molecular sieve pores, so that the catalyst shows good propane conversion rate and excellent propylene selectivity;
[0084] (3) The supported catalyst provided by the present invention is used in a supporting fixed-bed reaction process to dehydrogenate propane to produce propylene. The process is simple to operate, has excellent catalytic performance, high propylene selectivity, good stability, and good repeatability, and shows good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0085] Figure 1 This is the XRD spectrum of the nano-shuttle Silicate-2 molecular sieve prepared in Example 1;
[0086] Figure 2 N is the nano shuttle-shaped Silicate-2 molecular sieve prepared in Example 1 2 Physical adsorption and desorption curves;
[0087] Figure 3 This is a SEM scanning electron microscope image of the nano-shuttle-shaped Silicate-2 molecular sieve supported catalyst prepared in Example 1;
[0088] Figure 4 This is a TEM transmission electron microscope image of the nano-shuttle-shaped Silicate-2 molecular sieve supported catalyst prepared in Example 1;
[0089] Figure 5 This is a TEM transmission electron microscope image of the nano-shuttle-shaped Silicate-2 molecular sieve supported catalyst prepared in Example 3;
[0090] Figure 6 This is the propane dehydrogenation performance diagram of catalyst A6 prepared in Example 6. DETAILED DESCRIPTION
[0091] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0092] The specific implementation modes of the present invention will be explained and described below. It should be understood that the description of the specific implementation modes below is only used to explain and describe the present invention, but not to limit the present invention.
[0093] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0094] Embodiment 1:
[0095] Preparation of nano-shuttle-shaped Silicate-2 molecular sieve by hydrothermal method:
[0096] Weigh 41.05g of 10wt% tetrabutylammonium hydroxide solution and mix it with 5.47g of deionized water, then slowly drop 34.48g of tetraethyl orthosilicate into the mixed solution, and stir it for 12h at room temperature to completely hydrolyze the tetraethyl orthosilicate to form a uniform mixed gel; the corresponding molar ratio of each substance in the gel is SiO 2 :TBAOH:H 2 O=1:0.24:12. The gel solution was transferred into a 200mL hydrothermal autoclave and crystallized at 120℃ for 120h. After the hydrothermal autoclave was cooled to room temperature, the crystallized product was centrifuged at 5000rpm, washed with deionized water until pH=7.5, and then dried at 120℃ for 8h. Finally, the temperature was increased to 580℃ at a heating rate of 1-2℃ / min, and calcined at 580℃ for 6h. After crushing and grinding, a nano-fusilliform Silicate-2 molecular sieve was obtained, which was recorded as MEL-1.
[0097] Phase structure and N 2 The physical adsorption and desorption curves are shown in Figure 1 and Figure 2 The specific surface area, pore volume and pore size of the molecular sieve are shown in Table 1. Figure 1It can be seen that the structure of the synthesized molecular sieve is a pure phase MEL type Silicate-2 molecular sieve crystal form with good crystallinity; Figure 2 It is a typical type IV adsorption isotherm, P / P 0 The hysteresis loop in the range of =0.4-0.9 proves the existence of intercrystalline multi-level mesopores in the molecular sieve. The molecular sieve shows the distribution characteristics of multi-level pores. According to the DFT model calculation, the micropore diameter is mainly distributed in 0.5-1.0nm, and the intercrystalline multi-level mesopores are distributed in 2-30nm.
[0098] Impregnation of active components and additives: According to the Pt / Sn molar ratio of 1:3, weigh 0.188g of crystalline tin tetrachloride, dissolve it in 10mL of deionized water, and accurately measure 9.4mL of 0.019M chloroplatinic acid aqueous solution prepared in advance, add it to the above solution, and stir and mix it evenly; then weigh 7.0g of the above MEL-1 molecular sieve, add the mixed solution to the molecular sieve, stir it at room temperature and 500rpm speed to fully impregnate it, and keep the impregnation time for 4h. The impregnated sample was vacuumed (vacuum degree 72mbar) on a rotary evaporator with a water bath temperature of 70℃ and a speed of 120rpm to remove the solvent, placed in a drying oven at 100℃ for 8h, and moved into a muffle furnace at 580℃ for calcination for 6h to obtain a nano-shuttle-shaped Silicate-2 molecular sieve loaded with 0.5wt% Pt catalyst 0.5PtSn 3 / MEL-1, recorded as catalyst A1. Based on the total mass of the catalyst as 100wt%, the mass percentage of each metal component is Pt: 0.5wt%, Sn: 1.0wt%.
[0099] The SEM scanning electron microscope image and TEM transmission electron microscope image of catalyst A1 are shown in Figure 3 and Figure 4 .from Figure 3 It can be seen that the morphology of the catalyst is a nano-spindle sphere assembled by plugging rod-like microcrystals, and the particle size is uniform, with a statistical grain size between 200-250nm. Figure 4 It can be seen that the morphology of catalyst A1 is similar to Figure 3 The loaded active component Pt particles are evenly distributed on the surface of the carrier, and it is difficult to see the presence of obviously larger particles. The statistical particle size is 2-4nm, which indicates that the higher external specific surface area of the synthesized nano-fuselage Silicate-2 molecular sieve is significantly beneficial to improving the dispersion of the active components of the catalyst.
[0100] Embodiment 2:
[0101] The preparation of nano-fuselage Silicate-2 molecular sieve is the same as that in Example 1.
[0102] Impregnation of active components and additives: According to the Pt / Sn molar ratio of 1:3, weigh 0.188g of crystalline tin tetrachloride, 0.068g of potassium chloride, dissolve in 10mL of deionized water, and accurately measure 9.4mL of 0.019M chloroplatinic acid aqueous solution prepared in advance, add to the above solution, stir and mix thoroughly; then weigh 7.0g of the above MEL-1 molecular sieve, add the mixed solution to the molecular sieve, stir thoroughly at room temperature and 500rpm, impregnate evenly, and keep the impregnation time for 4h. The impregnated sample was vacuumed (vacuum degree 72mbar) on a rotary evaporator with a water bath temperature of 70℃ and a speed of 120rpm to remove the solvent, placed in a drying oven at 100℃ for 8h, and moved into a muffle furnace at 580℃ for calcination for 6h to obtain a nano-shuttle-shaped Silicate-2 molecular sieve loaded with PtSn 3 K catalyst PtSn 3 K / MEL-1, denoted as catalyst A2. Based on the total mass of the catalyst being 100 wt%, the mass percentage of each metal component is Pt: 0.5 wt%, Sn: 1.0 wt%, K: 0.5 wt%.
[0103] The morphology and active component crystal size of catalyst A2 are Figure 3 Basically, the Pt particle size is 2-10nm, and the active components on the carrier surface are well dispersed.
[0104] Embodiment 3:
[0105] The preparation of nano-fuselage Silicate-2 molecular sieve adopts the same method as in Example 1, except that the hydrothermal reaction temperature is increased to 160° C. The remaining operations and conditions are the same as in Example 1, and MEL-2 molecular sieve is prepared.
[0106] Impregnation of active components and additives: According to the Pt / Sn molar ratio of 1:3, weigh 0.188g of crystalline tin tetrachloride, dissolve it in 10mL of deionized water, and accurately measure 9.4mL of a 0.019M chloroplatinic acid aqueous solution prepared in advance, add it to the above solution, and stir and mix it evenly; then weigh 7.0g of the above MEL-2 molecular sieve, add the mixed solution to the molecular sieve, stir it at room temperature and 500rpm to fully impregnate it, and keep the impregnation time for 4h. The impregnated sample was evacuated (vacuum degree 72mbar) on a rotary evaporator with a water bath temperature of 70℃ and a speed of 120rpm to remove the solvent, placed in a drying oven at 100℃ for 8h, and moved into a muffle furnace at 580℃ for calcination for 6h to obtain a nano-shuttle-shaped Silicate-2 molecular sieve loaded with PtSn 3 The catalyst PtSn 3 / MEL-2, recorded as catalyst A3. Based on the total mass of the catalyst as 100wt%, the mass percentage of each metal component is Pt: 0.5wt%, Sn: 1.0wt%.
[0107] The TEM image of catalyst A3 is shown in Figure 5 As shown, it can be seen that its morphology and structure are Figure 3 Basically the same, but due to the increase of crystallization temperature, the relative crystallinity of the molecular sieve increases, the grain size increases, and the particle size distribution is between 280 and 350 nm; the Pt particles loaded on the surface of the molecular sieve are also evenly distributed, and the statistical particle size is 2-10 nm.
[0108] Embodiment 4:
[0109] Nano-shuttle Silicate-2 molecular sieve:
[0110] Weigh 24.24g of tetraethyl orthosilicate and slowly add it dropwise into 41.05g of 10wt% tetrabutylammonium hydroxide solution, and stir it thoroughly at room temperature for 12h to completely hydrolyze the tetraethyl orthosilicate to form a uniform mixed gel; the corresponding molar ratio of each substance in the gel is SiO 2 :TBAOH:H 2 O=1:0.15:15. The mixed gel solution was transferred into a 200mL hydrothermal autoclave and crystallized at 120℃ for 120h. The crystallized product was centrifuged at 5000rpm, washed with deionized water until pH=7.5, and then dried at 120℃ for 8h. Finally, the temperature was increased to 580℃ at a heating rate of 1-2℃ / min, and calcined at 580℃ for 6h. Silicate-2 molecular sieve was obtained after crushing and grinding, which was recorded as MEL-3.
[0111] Impregnation of active components and additives: Same as in Example 1, to obtain nano-fuselage Silicate-2 molecular sieve loaded with PtSn 3 The catalyst PtSn 3 / MEL-3, recorded as catalyst A4. Based on the total mass of the catalyst, the mass percentage of each metal component is Pt: 0.5wt%, Sn: 1.0wt%.
[0112] SEM morphology of catalyst A4 and Figure 3 The particles are consistent, showing a spindle-shaped sphere assembled by rod-shaped plug-in, with a grain size between 250-280nm; the loaded active component Pt particles are evenly distributed, with a statistical particle size of 2-10nm, and the active component is well dispersed.
[0113] Embodiment 5:
[0114] Preparation of nano-shuttle-shaped Silicate-2 molecular sieve by hydrothermal method:
[0115] Weigh 41.05g of 10wt% tetrabutylammonium hydroxide solution and mix it with 16.70g of deionized water, then slowly drop 54.94g of tetraethyl orthosilicate into the mixed solution, and stir it for 12h at room temperature to completely hydrolyze the tetraethyl orthosilicate to form a uniform mixed gel; the corresponding molar ratio of each substance in the gel is SiO 2 :TBAOH:H 2 O=1:0.30:15. The mixed gel solution was transferred into a 200mL hydrothermal autoclave and crystallized at 120℃ for 120h. The crystallized product was centrifuged at 5000rpm, washed with deionized water until pH=7.5, and then dried at 120℃ for 8h. Finally, the temperature was increased to 580℃ at a heating rate of 1-2℃ / min, calcined at 580℃ for 6h, and crushed to obtain Silicate-2 molecular sieve, which was recorded as MEL-4.
[0116] Impregnation of active components and additives: Same as in Example 1, to obtain Silicate-2 molecular sieve loaded with PtSn 3 The catalyst PtSn 3 / MEL-4, recorded as catalyst A5. Based on the total mass of the catalyst, the mass percentage of each metal component is Pt: 0.5wt%, Sn: 1.0wt%.
[0117] SEM morphology of catalyst A5 and Figure 3 The results are consistent, showing a spindle-shaped spherical shape assembled by rod-shaped plug-in, with a grain size between 200-220nm; the grain size is small, the specific surface area is significantly increased, the loaded active component Pt particles are evenly distributed, the statistical particle size is 2-10nm, and the active component is well dispersed.
[0118] Example 6
[0119] The preparation of nano-fuselage Silicate-2 molecular sieve is the same as that in Example 1.
[0120] Impregnation of active components and additives: According to the Pt / Sn molar ratio of 1:3, weigh 0.188g of crystalline tin tetrachloride and 0.151g of calcium chloride, dissolve in 10mL of deionized water, and accurately measure 9.4mL of 0.019M chloroplatinic acid aqueous solution prepared in advance, add to the above solution, stir and mix thoroughly; then weigh 7.0g of the above MEL-1 molecular sieve, add the mixed solution to the molecular sieve, stir thoroughly at room temperature and 500rpm, impregnate evenly, and keep the impregnation time for 4h. The impregnated sample was vacuumed (vacuum degree 72mbar) on a rotary evaporator with a water bath temperature of 70℃ and a speed of 120rpm to remove the solvent, placed in a drying oven at 100℃ for 8h, and moved into a muffle furnace at 580℃ for calcination for 6h to obtain a nano-shuttle-shaped Silicate-2 molecular sieve loaded with PtSn 3 K catalyst PtSn 3 K / MEL-1, denoted as catalyst A6. Based on the total mass of the catalyst, the mass percentage of each metal component is Pt: 0.5wt%, Sn: 1.0wt%, Ca: 0.5wt%.
[0121] The morphology and active component crystal size of catalyst A2 are Figure 3 and Figure 4 Basically, the Pt particle size is 2-10nm, and the active components on the carrier surface are well dispersed.
[0122] Comparative Example 1
[0123] Inorganic silica sol was used to replace organic tetraethyl orthosilicate, and the ratio was calculated according to the formula of silica sol: TBAOH: H 2 A mixed gel was formed with a molar ratio of 1:0.24:12 of O, and hydrothermally crystallized at 120°C for 120h. After cooling to room temperature, the crystallized product was centrifuged at 5000rpm, washed with deionized water to pH=7.5, and then dried at 120°C for 8h. Finally, the temperature was increased to 580°C at a heating rate of 1-2°C / min, calcined at 580°C for 6h, and crushed to obtain an inorganic silicon source hydrothermally prepared molecular sieve, which was recorded as MEL-5.
[0124] Impregnation of active components and additives: The same as in Example 1, to obtain the above molecular sieve loaded with PtSn 3 The catalyst PtSn 3 / MEL-5, recorded as catalyst D1. Based on the total mass of the catalyst, the mass percentage of each metal component is Pt: 0.5wt%, Sn: 1.0wt%.
[0125] Comparative Example 2:
[0126] Referring to the preparation method of Example 1, the active component and the auxiliary agent were co-impregnated on a commercially purchased ZSM-11 molecular sieve using an over-impregnation method, and the structural silicon-aluminum ratio was 40. The specific steps are as follows:
[0127] Weigh 7.0g of commercially available ZSM-11 molecular sieve, and add the mixed solution of active components and auxiliary components in Example 1 to the above molecular sieve, stir at room temperature and 500rpm to fully impregnate, and keep the impregnation time for 4h. The impregnated sample was evacuated (vacuum degree 72mbar) on a rotary evaporator at a water bath temperature of 70℃ and a rotation speed of 120rpm to remove the solvent, placed in a drying oven at 100℃ for 8h, and moved into a muffle furnace at 580℃ for calcination for 6h to obtain a commercially available ZSM-11 molecular sieve loaded with 0.5wt% PtSn 3 The catalyst is denoted as catalyst D2.
[0128] Comparative Example 3:
[0129] Referring to the preparation method of Example 1, the active component and the auxiliary agent are co-impregnated into the conventional γ-Al 2 O 3 On the carrier, the specific steps are as follows:
[0130] Weigh 7.0 g of γ-Al 2 O 3 Molecular sieve, add the mixed solution of active components and auxiliary components in Example 1 to the above molecular sieve, stir at room temperature and 500 rpm to fully impregnate, and keep the impregnation time for 4 hours. The impregnated sample is evacuated (vacuum degree 72mbar) on a rotary evaporator at a water bath temperature of 70°C and a rotation speed of 120rpm to remove the solvent, placed in a drying oven at 100°C for 8 hours, and moved into a muffle furnace at 580°C for calcination for 6 hours to obtain γ-Al 2 O 3 Loaded 0.5wt% PtSn 3 The catalyst is recorded as catalyst D3.
[0131] Test Example 1:
[0132] The phase structure analysis of the nano-fuselage Silicate-2 molecular sieve in the above Examples 1-6 was performed using an X-ray diffractometer model D8Advance from Bruker AXS, Germany. Figure 1 The nano-fusiform Silcate-2 molecular sieve in Example 1-2 was subjected to the N adsorption on the fully automatic adsorption apparatus model AutosorbiQ produced by the American company Quantachrome. 2 The physical adsorption-desorption curves were measured, and the specific surface area, pore volume and pore size distribution of the carrier corresponding to each catalyst sample in Examples 1-6 and Comparative Examples 1-3 were calculated. The results are shown in Table 1.
[0133] Table 1:
[0134]
[0135] In Table 1, S Micro Refers to the micropore specific surface area of the molecular sieve carrier used in the synthesis of each catalyst; S Ext Refers to the external specific surface area of the synthetic molecular sieve carrier; S BET Refers to the total specific surface area of the synthetic molecular sieve carrier; V Micro Refers to the micropore volume of the synthetic molecular sieve carrier; V meso Refers to the mesopore volume of the synthetic molecular sieve carrier; V Total Refers to the total pore volume of the molecular sieve carrier.
[0136] Test Example 2:
[0137] The catalysts in Examples 1-6 were analyzed by scanning electron microscopy using a Hitachi S-4800 cold field emission scanning electron microscope. Figure 3 ; The transmission electron microscopy analysis of each catalyst was carried out on the Tecnai20 model of FEI Company of the Netherlands, for example, see Figure 4 and Figure 5 .
[0138] Test Example 3:
[0139] The catalyst of the present invention was tested and evaluated in a constant temperature micro fixed bed reactor. The evaluation conditions were as follows: about 0.5 g of the catalyst was mixed with 10 g of quartz sand in sections and loaded into a quartz tube reactor with an inner diameter of Ф=10 mm. The reaction pressure was normal pressure, and the reaction gas was H 2 Dilution, propane gas mass space velocity is 3h -1 , H 2 The feed pressure ratio to propane was 1:4, and the reaction temperature was 600°C. The products were analyzed for distribution of reaction products using Agilent 7890A gas chromatograph.
[0140]
[0141]
[0142] The propane dehydrogenation performance evaluation results of each catalyst in the above Examples 1-6 and Comparative Examples 1-3 are shown in Table 2. Table 2 shows the propane conversion rate and propylene selectivity when the sample is stabilized for about 5 hours after the catalytic induction reaction for 30 minutes. The propane dehydrogenation performance of catalyst A6 in Example 6 is shown in Table 2. Figure 6The catalyst showed high propane conversion and excellent propylene selectivity in the process of catalytic propane dehydrogenation, and the catalyst maintained good stability during the 20-hour reaction process; its propane conversion was still above 95% of the initial level, and the propylene selectivity was maintained at 97.5%; while the initial activity of catalyst D3 was affected by Al 2 O 3 The strong acidity of the carrier surface can promote the occurrence of carbon deposition side reactions such as hydrogenolysis and cracking. The initial conversion rate is high, and the propylene selectivity is only 86.6%. After 20 hours of continuous catalytic reaction, the conversion rate will be lower than 70% of the original conversion rate, and the propylene selectivity will be maintained at 90%.
[0143] Table 2:
[0144] catalyst Reaction time (h) Propane conversion rate / (%) Propylene selectivity / (%) A1 5 31.0 97.6 A2 5 32.9 97.8 A3 5 24.2 97.7 A4 5 29.8 97.4 A5 5 30.6 98.0 A6 5 43.4 97.7 D1 5 19.3 97.8 D2 5 26.7 31.7 D3 5 38.9 86.6
[0145] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
[0146] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
[0147] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0148] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0149] The endpoints and any values of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.
[0150] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
[0151] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.
Claims
1. A nano-shuttle Silicate-2 molecular sieve supported catalyst, the catalyst comprising a carrier and an active component and an auxiliary component supported on the carrier, the active component being selected from at least one of the noble metal elements of Group VIII; the auxiliary component being selected from one or more of the metal elements of Group IVA, Group IA, and Group IIA; in, The carrier is a Silicate-2 molecular sieve having a nano-shuttle shape.
2. The catalyst according to claim 1, characterized in that: The Silicate-2 molecular sieve has a particle size of 180-500 nm and a specific surface area of 550 m 2 / g or more, of which the external specific surface area is 180-450m 2 / g, pore volume at 0.5cm 3 / g or more, the pores present a multi-level pore distribution; preferably, the Silicate-2 molecular sieve has at least one of the following characteristics: The particle size of the Silicate-2 molecular sieve is 200-350 nm; and / or, The specific surface area of the Silicate-2 molecular sieve is 550-700m 2 / g; and / or, The pore volume of the Silicate-2 molecular sieve is 0.5-1.5 cm 3 / g; and / or, The pores of the Silicate-2 molecular sieve present a multi-level pore distribution, with micropores having a pore size distribution of 0.5-2.0 nm and multi-level mesopores between crystals having a pore size distribution of 2-40 nm; preferably, the micropores have a pore size distribution of 0.5-1.0 nm and multi-level mesopores between crystals have a pore size distribution of 2-30 nm.
3. The catalyst according to claim 1, characterized in that: The Silicate-2 molecular sieve presents a shuttle-shaped morphology assembled by plugging rod-shaped microcrystals, and the preferred crystal size is 200-400 nm; and / or, The Silicate-2 molecular sieve is an all-silicon MEL structure molecular sieve.
4. The catalyst according to claim 1, characterized in that: The Silicate-2 molecular sieve is prepared by the following method: the preparation method of the Silicate-2 molecular sieve comprises subjecting a mixture containing a silicon source, a template and water to hydrothermal crystallization treatment, cooling the obtained reaction mixture, and then subjecting the mixture to solid-liquid separation, optional washing, optional drying, and calcination to obtain the Silicate-2 molecular sieve.
5. The catalyst according to claim 4, characterized in that The preparation method of the Silicate-2 molecular sieve comprises the following steps: (1) mixing a silicon source, a template and water to form a mixed gel; (2) subjecting the mixed gel to a hydrothermal crystallization treatment to obtain a reaction mixture; (3) After the reaction mixture is cooled, solid-liquid separation, optional washing, optional drying, and calcination are performed to obtain the Silicate-2 molecular sieve.
6. The catalyst according to claim 4, characterized in that: The molar ratio of the silicon source to the template and water in terms of SiO2 is 1:(0.10.5):(10-50), more preferably 1:(0.150.4):(10-30); and / or, The silicon source is an organic silicon source, preferably at least one selected from tetraethyl orthosilicate, tetraethyl orthosilicate, tetraethyl silicate-28, and tetraethyl silicate-40; and / or, The template agent is one or more of tetrabutylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium fluoride and cyclohexylamine; and / or, The mixing conditions in step (1) include: temperature of 20-30° C., time of 3-12 h; preferably, the stirring speed is 400-600 rpm relative to 10 g of the mixture system.
7. The catalyst according to claim 4, characterized in that: The conditions of the hydrothermal crystallization treatment include: a temperature of 120-190° C., preferably 120-170° C., and / or a time of 36-150 h; and / or, The calcination conditions include: heating to 500-600°C, preferably 550-580°C, at a heating rate of 1-2°C / min; and calcination time of 4-6h.
8. The catalyst according to any one of claims 1 to 7, characterized in that: The active component is selected from at least one of Pt, Ir, Au, Pd and Rh; and / or, The auxiliary component is selected from at least one of Group IVA metal elements, Group IA alkali metal elements, and Group IIA alkaline earth metal elements; preferably, the auxiliary component is selected from at least one of Sn, Na, K, Rb, Cs, Mg, Ca, and Sr.
9. The catalyst according to any one of claims 1 to 7, characterized in that: The morphology of the catalyst is nano-spindle-shaped spheres assembled by plugging rod-shaped microcrystals; and / or, The size of the catalyst is 200-500 nm; and / or, The particle size of the active component in the catalyst is 2-10 nm; and / or, Based on the total mass of the catalyst as 100wt%, the loading amount of the active component is 0.1wt%-1.0wt%, preferably 0.1wt%-0.5wt%; and / or, the loading amount of the metal element of Group IVA is 0.1wt%2.0wt%, preferably 0.1wt%-1.5wt%; and / or, the loading amount of the metal element of Group IA is 0wt%1wt%, preferably 0.1wt%-1.0wt%; and / or, the loading amount of the metal element in Group IIA is 0-2.0wt%, preferably 0.1wt%-1.0wt%.
10. A method for preparing the catalyst according to any one of claims 1 to 9, comprising loading the active component source and the auxiliary component source on the carrier, and then calcining to obtain the catalyst.
11. The preparation method according to claim 10, characterized in that: The calcination conditions include: heating at a rate of 1-2°C / min to a temperature of 550-600°C, and a calcination time of 4-6h; and / or, The loading method is to immerse the carrier in a solution containing the active component source and the auxiliary component source, and then remove the solvent; preferably, The solution containing the active component source and the auxiliary component source is an aqueous solution; further preferably, The active ingredient source is water-soluble; and / or, The auxiliary component source is water-soluble.
12. Use of the catalyst according to any one of claims 1 to 9 or the catalyst obtained by the preparation method according to any one of claims 10 to 11 in propane dehydrogenation catalysis.
Citation Information
Patent Citations
Catalyst for preparing propylene through propane catalytic dehydrogenation and preparation method thereof
CN102389831A
Propane dehydrogenation catalysts and their preparation methods, as well as methods for propane dehydrogenation to propylene.
CN109746028B
Pt-based multi-component catalyst for preparing propylene by propane dehydrogenation, and preparation method thereof
CN111790384A
High-temperature and ball-milled modified SBA-15 molecular sieve materials and their preparation methods, propane dehydrogenation catalysts and their preparation methods and applications
CN112138705B
A composite molecular sieve catalyst for propane dehydrogenation to olefins and its preparation method
CN112206816B